Esophagitis and almost complete esophageal occlusion in a girl with epidermolysis bullosa - Djurić, Zlatko; Nagorni, Aleksandar; Zivanović, Dragoljub (The Turkish Journal of Pediatrics, 2012)
Epidermolysis bullosa is a genetically transmitted skin disorder that typically manifests with trauma-induced skin blistering, scarring and in some cases mucosal involvement. Esophageal webs, strictures or stenosis can be found in about a third of the patients with the recessive dystrophic type of this disease. We report a six-year-old girl with recessive dystrophic epidermolysis bullosa and progressive dysphagia. Almost complete esophageal occlusion was found on barium swallow and esophagoscopy (endoscopic signs of esophagitis were also seen). She was treated successfully with fluoroscopically guided balloon dilatation and esomeprazole. Fluoroscopically guided balloon dilatation and postdilatation use of esomeprazole is a safe and effective therapy for recessive dystrophic epidermolysis bullosa patients with almost complete esophageal occlusion and esophagitis.